NITROGÊNIO: NUTRIENTE OU POLUENTE? - Carvalho, Nathália Leal; Zabot, Valdirene (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704671 The rational use of fertilizers, especially nitrogen in search of productivity growth, hasbeen gaining increasing importance in activities related to Brazilian agriculture. However, for thisgoal is reached, it is necessary a more comprehensive understanding of the various factorsaffecting the efficient use of fertilizer. In turn the areas used for agricultural cultivation worldwidefertilizers contain too much - or less. And the two extremes imply high costs for both theenvironment and man himself. One of the most limiting nutrient for crop production is nitrogen(N). Some poor people are starving in the world simply because there is a sufficient amount of Nto adequately feed their crops. On the other hand, in certain regions of our planet, there is anexcess of N. That is, this nutrient is supplied to crops in a much larger amount than necessary. Inthese situations, the N becomes a pollutant because its presence in excess triggers a series ofreactions and processes that are extremely harmful to the environment and thus the health ofpopulations. In order to understand the dynamics of N and how it can become pollutants carriedto the present work.